2021
DOI: 10.1016/j.jmmm.2021.167813
|View full text |Cite
|
Sign up to set email alerts
|

Vortex structure in magnetic nanodots: Dipolar interaction, mobile spin model, phase transition and melting

Abstract: We study in this article properties of a nanodot embedded in a support by Monte Carlo simulation. The nanodot is a piece of simple cubic lattice where each site is occupied by a mobile Heisenberg spin which can move from one lattice site to another under the effect of the temperature and its interaction with neighbors. We take into account a short-range exchange interaction between spins and a long-range dipolar interaction. We show that the ground-state configuration is a vortex around the dot central axis: t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…They observed six-fold degenerate spin states because of dipolar interaction [21]. Bailly-Reyre et al found ground-state configuration to be a vortex in the cubic assembly of nanodots [22]. Luttinger et al observed the minimum energy configurations to be ferromagnetic in a face-centred cubic lattice [23].…”
Section: Introductionmentioning
confidence: 99%
“…They observed six-fold degenerate spin states because of dipolar interaction [21]. Bailly-Reyre et al found ground-state configuration to be a vortex in the cubic assembly of nanodots [22]. Luttinger et al observed the minimum energy configurations to be ferromagnetic in a face-centred cubic lattice [23].…”
Section: Introductionmentioning
confidence: 99%